On the People of the Book (The Armenian Theme in Boris Slutsky’s Poetry) - KUBATIAN, GEORGY (Bulletin of Yerevan University H: Russian Philology, 2021)
Boris Slutsky is a writer of frontline generation, one of the greatest Russian poets of second half of XX century. He translated poems by Armenian poets, published reviews and comments on their work. The article analyzes the Slutsky’s poems on the Armenian theme. They don՛t constitute a single cycle and written at different times, and it indicates a constancy of interest to Armenia. Some of these poems have a high artistic value.
Keywords: frontline generation, monument to the alphabet, Hakob Kojoyan, Harutun Kalents